Rare clinical forms of chronic brucellosis - N. Yu. Pshenichnaya; G. V. Gopatsa; T. V. Sergeeva (Журнал инфектологии, 2023)
Brucellosis is the most common and severe infectious disease in the group of zoonotic infections. This disease is characterized by a multisysitemic lesion. The difficulties in diagnosing this disease are associated with the pathogenetic features of the development of brucellosis, namely prolonged bacteremia, which causes the development of secondary foci of infection in various organs and tissues, manifested by a variety of clinical manifestations, the erasure of symptoms of the disease, as well as the appearance of rare clinical forms of brucellosis.One of the rare clinical manifestations of chronic brucellosis is the defeat of the cardiovascular system and the defeat of the nervous system. According to the latest literature data, cardiovascular complications of brucellosis in humans account for only 3%, but are the main cause of death in 80%. Damage to the nervous system is rare, with a registered frequency of 3% to 13%.Clinical manifestations of neurobrucellosis are diverse and can mimic many other neurological diseases. The most common manifestations of brucellosis may be meningitis, meningoencephalitis. Despite the rare occurrence, these forms of the disease are severe, lead to disability and mortality with late diagnosis. The article presents clinical cases of brucellosis with lesions of the heart and central nervous system.